Przedmiot zarządzania kapitałem obrotowym netto w świetle maksymalizacji wartości dla właścicieli - Wawryszuk, Anna (Subject of Working Capital Management in Respect of Maximizing of Shareholders Value, 2006)
Maximizing of shareholders value is now the main goal of corporates. Therefore, many firms develop and implement value-based strategies. The overall corporate strategy has three supporting pillars, i.e. profitability, liquidity and growth, which should be built in the process of financial management. The way working capital is managed has a significant impact on the three supporting pillars. The purpose of working capital management is clear, but the main problem is how to do it. Firstly there is a need to realize that working capital is the effect of a lot of processes that generate cash flows. This article shows that this process can be divided into two groups, so the object of working capital management can be defined in two different ways.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 673-682